Hindgut Duplication: A Unique Case of Six Perineal Openings - Haq, Shujaul (Cureus, 2017)
Complete hindgut duplication is a rare and intriguing entity, often coupled with genitourinary abnormalities and neural tube defects. The diagnosis demands a thorough clinical exam and radiological workup. Timely recognition and expeditious treatment of these patients can lead to a better quality of life. We present a case of a 10-month-old female with complete hindgut duplication and associated genitourinary duplication treated with surgical intervention.